Feasibility and Safety of Laparoscopic Appendectomy Performed by Residents with No Experience in Open Appendectomy - Yamamoto, Ryusei (JMA J, 2019)
INTRODUCTION: Open appendectomy for acute appendicitis is a common procedure for surgical residents to perform at the beginning of their training. Recently, many programs have moved to laparoscopic appendectomy as the initial training procedure. However, the feasibility and safety of laparoscopic appendectomy for acute appendicitis performed by surgical residents without any experience of open appendectomy remains controversial. METHODS: The records of patients who underwent laparoscopic appendectomy for acute appendicitis between August 2006 and March 2017 were retrospectively reviewed. Patients were assigned to two groups according to whether their procedure was performed by a surgical resident, with no experience of open appendectomy, or a surgical fellow, with adequate open appendectomy experience but no experience with laparoscopic appendectomy. RESULTS: A total of 130 patients were included. Five residents performed 104 procedures, and three fellows performed 26 procedures. The baseline patient characteristics were comparable between groups. The median operative time was comparable (77.0 min vs. 65.5 min; p = 0.771). There were no significant differences in overall complications; with 14 patients (13%) in the resident group and five patients (19%) in the fellow group experienced complications (p = 0.535). No patient required reoperation, and there were no fatalities. The median length of stay was similar (5.0 days vs. 5.5 days; p = 0.430). CONCLUSIONS: Laparoscopic appendectomy for acute appendicitis is feasible and safe when performed by surgical residents with no prior open appendectomy experience. It may be performed as the first procedure during surgical training with no adverse effect on patients.